Disturbing Facts in James Oliver v McDonald: Re-Examine the Lean Finely Textured Beef (LFTB) from Halalan Tayyiba Perspectives - Hakimah Yaacob; Nurul Aini Muhamed; Muhammad Iqmal Hisham Kamaruddin (USIM Press, 2024)
Readings in Sustaining Global Halal Ecosystem : (Collection of Articles from The 2nd International Halal Management Conference)